Elaboración de un manual para el desarrollo de páginas web aplicando la iniciativa de accesibilidad web (wai) - Álvarez Olvera, Jorge Víctor (2016)
The next project titled "Development of a manual for the development of web pages using the Web Accessibility Initiative (WAI)." Was held at the State Technical University of Quevedo with the purpose that the web and practitioners designers have with this investigation as a reference source of new web technologies, which is very important this work, which will be for people who are interested in acquiring new knowledge in web development. During the conduct of this research was a study of the Accessibility Guidelines Web Content (WCAG), this allowed us to carry out a job that has benefits for Web developers, both money and time, this manual is a tool teaching quality information on teaching create accessible web pages. Adobe package for both the design and the layout of it was used for carrying out the manual. This manual can be manipulated by different users easily to guide you step by step how to create attractive and accessible websites by visitors.